A Novel Voltage Divider Circuit - Selvam, K. C.; Latha, S. (Engineering, Technology & Applied Science Research, 2012)
A novel analog divider is described in this paper. The circuit enables the division of a dc voltage with another dc voltage. The constant of the division is dependent upon a third dc voltage and a pair of resistors. Employing a precision source for the third dc voltage and matched resistors, an acceptable level of accuracy can be obtained.